2015
DOI: 10.5539/ijms.v7n4p105
|View full text |Cite
|
Sign up to set email alerts
|

Structural Equation Modeling of E-Service Recovery Satisfaction and Customer Retention in the Airline Industry in Malaysia

Abstract: In the age of the internet, customer retention has become a crucial element in firms' survival. Losing customers to competitors in the e-context is a constant threat, as the potential for this loss is 'only a click away'. The current study suggests two new constructs, accumulative trust and digital commitment as customer determinants appropriate for the online context. This study aims to investigate the effect of three customer determinants (accumulative trust, customer perception of feedback and digital commi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Satisfactory service recovery outcomes enhance the perceived material and psychological benefits of providing online reviews, which might then motivate the consumers to engage further in eWOM communication (Kim et al, 2009;Ro & Wong, 2012). After all, higher recovery satisfaction implies a better service recovery experience associated with more perceived benefits (Al-Jader, 2015). Consumers who are more satisfied with their service recovery experience are likely to give eWOM review feedback more regularly, perhaps leading to habitual behaviour.…”
Section: Online Service Recovery and Future Ewom Media Engagementmentioning
confidence: 99%
“…Satisfactory service recovery outcomes enhance the perceived material and psychological benefits of providing online reviews, which might then motivate the consumers to engage further in eWOM communication (Kim et al, 2009;Ro & Wong, 2012). After all, higher recovery satisfaction implies a better service recovery experience associated with more perceived benefits (Al-Jader, 2015). Consumers who are more satisfied with their service recovery experience are likely to give eWOM review feedback more regularly, perhaps leading to habitual behaviour.…”
Section: Online Service Recovery and Future Ewom Media Engagementmentioning
confidence: 99%
“…It also aimed to examine further the relationships between justice dimensions, ECM, learners' satisfaction and continuance intention in one research model. In addition, this study empirically tested the relationships in the proposed model, thus further enriching the existing research and bridging the gaps identified in previous research (Rafah et al, 2015).…”
mentioning
confidence: 80%
“…Brand trust plays a significant role to ensure the certainty of products or services and maintain a confident relationship with the brand (Sambath and Jeng, 2015). Brand trust encourages customers to prefer a particular brand in a marketplace in presence of alternatives (Al–Jader and Sentosa, 2015; Husain et al. , 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Brand trust plays a significant role to ensure the certainty of products or services and maintain a confident relationship with the brand (Sambath and Jeng, 2015). Brand trust encourages customers to prefer a particular brand in a marketplace in presence of alternatives (Al-Jader and Sentosa, 2015;Husain et al, 2022). Brand trust is a confident expectation of brands' reliability to perform in uncertain situation and also the belief of customers that a particular brand serves their needs better than competing brands (Zhang et al, 2021).…”
Section: Brand Trustmentioning
confidence: 99%